On the translation of swearing into Spanish : Quentin Tarantino from Reservoir Dogs to Inglourious Basterds /: Quentin Tarantino from Reservoir Dogs to Inglourious Basterds. (2015) - Soler-Pardo, Betlem
No abstract available